Urban Design Interventions Towards a Bike Friendly City - Andrade, Victor; Haarder, Henrik (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
This paper`s goal is to present findings of the research project titled Bikeability, funded by the Danish Research Council, concerning the investigation of how Urban Design interventions in consolidated urban areas can promote cycling – with a special focus on alterations in the urban fabric and design qualities of the streetscape. The research focuses on a bike infrastructure with a distinct typology: Hans Broges Gade in Aarhus where a dedicated bike lane function as an extension of a bicycle route linking the suburb to Aarhus Central Station. Based on the data collected and analyzed, it was possible to identify the design qualities of the intervention and the impacts of the intervention in the travel behavior of the cyclists. A conjugation of sources of data was used: questionnaires, interviews with key actors, visual analysis of the site, counting, etc. The findings highlight important factors such as the relevance of fast connectivity, the aesthetic value of the streetscape and the safety for cyclists. Therefore, these three qualities are strategic dimensions of a design solution that must be taken in consideration by architects, planners and engineers. Bridging research and policy, the findings of this research project can also support bike friendly design and planning, and cyclist advocacy.